Hubungan Pengetahuan dan Sikap Masyarakat Tentang Penyakit Demam Berdarah Dengue Dengan Pencegahan Vektor di Kelurahan Malalayang 1 Barat Kota Manado - Ayudhya, Putri; Ottay, Ronald I; Kaunang, Wulan P.J.; Kandou, Grace D.; Pandelaki, A.J. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Dengue Hemoraic Fever is a one of the problem in Indonesia society and it’s patients are always increase and widen.Dengue Hemoragic Fever is also a disease caused base on enviroment. One of the factor of high mortality and morbilityrate are sociaty attitudes and its increased the risk of Dengue Hemoragic Fever spreading. Purpose : To find out therelation between knowleadge and attitude about Dengue Hemoragic Fever with vector preventive act in distric 1 westMalalayang Manado. Metode of the research The research was held from November-Desember 2013. The methode ofthe reseach is analytic desriptive with cross sectional design. The simple are sociaty who lived in district 1 west Malalayangand the number of sample are 100 person. The data analyst with univariate and bivariate and the statistic testare chi square. Result of the research : A part of the responden have a good knowledge about Dengue Hemoragic Feverdisease (96%), good attitude (98%) and Dengue Hemoragic Fever vector preventive act (99%). p value = 0,042 got bychi square test which means the are ralation between knowledge and attitude of vector preventive, and also p value =0,021 god by chi square which means the are significant relation between attitude and act. Conclution : There are betweenknowledge of Dengue Hemoragic Fever and vevtor prevention act and significant relation between DengueHemoragic Fever disease and vector preventive act.Keywords: Knowledge, Attitude, Act, Vector, Dengue Hemoragic Fever Disease, Distric 1 West Malalayang Manado